The Effectiveness Of School Buses In Supporting The Save Our Student (Sos) Program In Surabaya City - Dewi, Sarah Pramesti Puspa; Manggalou, Singgih (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
As a public servant, the government is obliged to provide services to the community, including service delivery. One of the essential public services the community requires is the provision of public transportation. Transportation is crucial in daily life, impacting the economic, social, health, and educational sectors. Surabaya, as one of the most densely populated cities in Indonesia, needs to provide public transportation services that facilitate accessibility to various sectors, especially education. The school bus service is specifically designed for students who are legally ineligible to drive, thus enabling them to reach school safely and efficiently. The School Bus in Surabaya is a public transportation service dedicated to students in support of the Save Our Student (SOS) program. This study employs a qualitative research method with a case study approach, aiming to provide an in-depth description of the school bus service in Surabaya. Data collection techniques include observation, interviews, and documentation. This study uses purposive sampling, where the researcher selects respondents most likely to provide relevant information on the discussed topic. The research findings indicate that the school bus service provided by the Surabaya City Transportation Department has not been effective in terms of target accuracy, goal achievement, and tangible changes. However, regarding program understanding and timeliness, the Surabaya City Transportation Department has provided good service to students, such as through socialization and the regularity of responsible staff. Therefore, it can be concluded that the effectiveness of the school bus service in Surabaya is not yet optimal.